Analisis Nilai Karakter Kesopanan dan Kesantunan Siswa Kelas V SD Negeri Purwoyoso 04 pada Penerapan Peraturan 5S di Sekolah - I, Intan; Dwi, Melda; Natasya, Juninta; Sari, Rezza; Maryatul, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine and analyze the politeness and politeness character values of class V students at SD Negeri Purwoyoso 04 through the implementation of 5S regulations at school. This research uses a qualitative descriptive method with data collection techniques carried out by means of observation, interviews and documentation. The results of the research show that the implementation of 5S regulations at SD Negeri Purwoyoso 04 is as follows: a) When arriving at the school gate, students get off their bicycles and shake hands and greet the picket teacher standing at the school gate, b) Students give a smile to the teacher who is standing at the school gate. welcoming his arrival to school, c) Students who are late for class say hello first before entering class and then shake hands with the class V teacher, d) When meeting the teacher outside the classroom, students greet him by giving a greeting. However, it cannot be denied that there are challenges in implementing politeness and politeness values through the 5S regulations, including students who still feel embarrassed or are reluctant to interact. Consistent efforts and patience from the school are very important to overcome this. Along with the 5S regulations, there has been a positive change in students' attitudes. Although there are still some students who have not fully adapted, there has been an increase in awareness of the importance of being polite and polite.